Comparison of some methods of testing hypothesis in unbalanced split plot design - Usman, Mustofa; Elfaki, Faiz Ahmed Mohamed; Daoud, Jamal Ibrahim; Agung, Hadi; Ruswandi, Rudi (2006)
Missing observations in split plot design create many analysis problems. In this article, we consider the testing hypotheses problems for a split plot design with missing subplots and whole plots. Some methods of testing hypotheses in unbalance split plot design are presented and the performances of the methods are compared based on the type I error and its power of the test. Simulation studies were conducted to compare the performance of various methods